Transitional Justice in Aparadigmatic Contexts Accountability, Recognition, and Disruption (Taylor & Francis, 2023)
Transitional Justice, Aparadigmatic Contexts, Transition
English
Keywords: thema EDItEUR::G Reference, Information and Interdisciplinary subjects::GT Interdisciplinary studies::GTU Peace studies and conflict resolution; thema EDItEUR::J Society and Social Sciences::JB Society and culture: general::JBF Social and ethical issues::JBFK Violence and abuse in society; thema EDItEUR::J Society and Social Sciences::JK Social services and welfare, criminology::JKV Crime and criminology; thema EDItEUR::J Society and Social Sciences::JW Warfare and defence::JWX Other warfare and defence issues::JWXK War crimes; thema EDItEUR::L Law::LB International law; thema EDItEUR::L Law::LN Laws of specific jurisdictions and specific areas of law::LNF Criminal law: procedure and offences; Transitional Justice, Aparadigmatic Contexts, Transition